PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN(STUDI KASUS PADA PT. INDOTIRTA ABADI DI GEMPOL PASURUAN) - MELIZAWATI (Jurnal Akuntansi AKUNESA, 2015)
This study aims effect to examine of organizational commitment to employee performance PT.INDOTIRTA ABADI Gempol, Pasuruan.The study was conductes using a questionairs survey on PT.INDOTIRTA ABADI. The data was collected by distributing questionairs to the respondents. Questionnairs distributed to 50 respondents. But only 30 respondents who fill out the questionnairs. The analytical tool used is SPSS.The results showed that : (1) organizational commitment was effect to employee performance.Keywords : Organizational Commitment , Employee Performance